Improving Nurse Documentation Time via an Electronic Health Record Documentation Efficiency Tool - Will, John; Jacques, Deborah; Dauterman, Denise; Torres, Rachelle; Doty, Glenn; O'Brien, Kerry; Groom, Lisa (Applied Clinical Informatics, 2025)
Nursing documentation burden is a growing point of concern in the United States health care system. Documentation in the electronic health record (EHR) is a contributor to perceptions of burden. Efficiency tools like flowsheet macros are one development intended to ease the burden of documentation.This study aimed to evaluate whether flowsheet macros, a documentation efficiency tool in the EHR that consolidates documentation into a single click, reduces the time spent on documentation activities and the EHR overall.Nurses in the health system were encouraged to create and utilize flowsheet macros for their documentation. Flowsheet documentation and time in system data for nurses' first and last shifts in the evaluation period were extracted from the EHR. Linear regression with control variables was utilized to understand if the utilization of flowsheet macros for documentation reduced the time spent in flowsheets or the EHR.The results of linear regression showed a significant, negative relationship between flowsheet macros use and time in flowsheets (adjusted odds ratio [AOR] = −0.291, 95% confidence interval [CI] = −0.342 to −0.240, p < 0.001). Flowsheet macros use and time in system also had a significant, negative relationship (AOR = −0.269, CI = −0.390 to −0.147, p ≤ 0.001). Subgroups for department specialties showed time savings in flowsheet activities for medical surgical, critical care, and obstetrics units, however, a significant relationship was not found in emergency and rehabilitation units.Utilization of flowsheet macros was associated with a decrease in the amount of time a nurse spends in both flowsheets and the EHR. Adoption and timesavings varied by the department setting, suggesting flowsheet macros may not be applicable to all patient types or conditions. Future research should investigate if the time savings from this tool yield benefits in perceptions of nurse documentation burden.
Keywords: nursing; documentation burden; electronic health record; efficiency